Effect of Elastomer Filling on the Tensile, Compressive, and Flexural Strength of Cross-Lattice Structured Acrylonitrile Styrene Acrylate Specimens Fabricated via Fused Filament Fabrication - Han, Kubilay; Kesercioglu, Muhammed Asim; Akin, Yasin; Cay, Yusuf; Tanyeri, Burak (Springer, 2025)
In this study, the effect of elastomer filling on the mechanical properties of lattice-structured specimens produced with ASA (acrylonitrile styrene acrylate) filament using the FFF method was investigated. Specimens were fabricated with varying lattice infill densities (20%, 30%, 40%), nozzle temperatures (260, 270, 280 degrees C), and elastomer ratios (1:1, 2:1, 3:1). Tensile, flexural, and compressive tests were conducted. Some specimens were left unfilled, while others were filled with elastomer, contributing to the originality of the study. The results demonstrated that elastomer filling significantly enhanced the mechanical performance of the specimens. Improvements of 15% in tensile strength, 19% in flexural strength, and 6% in compressive strength were observed with elastomer-filled lattice structures. Regarding the effect of parameters, elastomer filling provided notable improvements in tensile, flexural, and compressive strengths at low lattice infill densities (20%). However, at high infill densities (40%), the impact of the elastomer was limited due to structural stability. Additionally, increased nozzle temperature improved mechanical strength by enhancing interlayer bonding. This study highlights the detailed effects of elastomer filling on mechanical performance, contributing to new design and manufacturing approaches for engineering applications requiring flexibility and energy absorption.
Keywords: additive manufacturing; elastomer; fused filament fabrication; lattice structure